Pipe drafting and design - Parisher, Roy A. (Elsevier, 2012)
Pipe Drafting and Design, Third Edition provides step-by-step instructions to walk pipe designers, drafters, and students through the creation of piping arrangement and isometric drawings. It includes instructions for the proper drawing of symbols for fittings, flanges, valves, and mechanical equipment. More than 350 illustrations and photographs provide examples and visual instructions. A unique feature is the systematic arrangement of drawings that begins with the layout of the structural foundations of a facility and continues through to the development of a 3-D model. Advanced chapters d.